Human Capital Growth - with Region and Gender in Perspective - Gang Liu; Barbara M. Fraumeni; Shunsuke Managi (Institute of Labor Economics (IZA), 2022)
Chapter 6 from the forthcoming Inclusive Wealth Report 2022 looks at human capital in greater detail, based on the latest human capital estimates from the Inclusive Wealth Report (IWR) project. In the chapter, which is repeated here, the growth of human capital and several of its constituent factors are broken down by gender and by region, and in some cases also by income, since apparently, human capital in the world is not evenly distributed across different regions or countries by income, or between educated males and females, although in almost all country cases total and per capita human capital have grown over time. The purpose is to identify the sources of human capital growth by region, gender, and various determining factors over the observed time period, 1990-2020.
Keywords: E24; J16; O57; E01; 330; country wealth; human capital; analysis by regions and country income; gender; analysis by regions and country income